Age determination in the arctic fox ( Alopex lagopus ) - Bradley, J. A.; Secord, D.; Prins, L. (Canadian Journal of Zoology, 1981)
Canine teeth from foxes (Alopex lagopus) trapped in the Canadian arctic were aged by counting annular layers in the cementum. Of 513 teeth examined by this method, 448 were from foxes <1 year of age. Only 11% of those caught in February of their first year had a developing incremental line, compared with 77% in foxes >1 year. Simple linear measurement of the anteroposterior width of the pulp cavity was found to be an accurate method of aging 80% of juveniles.